2013
DOI: 10.1074/jbc.m112.411603
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Thalassemia/Mental Retardation Syndrome X-linked Gene Product ATRX Is Required for Proper Replication Restart and Cellular Resistance to Replication Stress

Abstract: Background: ATRX is involved in genome maintenance. Results: Somatic ATRX knock-out cells displayed hypersensitivity to hydroxyurea (HU) and defects in checkpoint activation and replication restart. Conclusion: ATRX is required for replication stress tolerance, proper checkpoint activation, and replication restart at stalled replication forks. Significance: These results reveal an unanticipated role of ATRX in maintaining genomic stability upon replication stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 41 publications
(23 reference statements)
10
99
0
Order By: Relevance
“…Ablation of ATRX in mouse myoblasts delayed their progression in S phase and led to an accumulation of DNA damage including telomere fragility [6] and similar findings were observed in a study involving neuroprogenitors [24]. In a further advance, a somatic knockout of ATRX in a colorectal cell line exhibited increased sensitivity to hydroxyurea and aphidicolin suggesting that in the absence of ATRX there is an increase in replicative stress in this cellular context [25]. Taken together with the findings presented here it is clear that ATRX has a general role in facilitating DNA replication in multiple cellular environments and that this may in part account for why loss of ATRX function results in such disparate pathologies.…”
Section: Discussionsupporting
confidence: 60%
“…Ablation of ATRX in mouse myoblasts delayed their progression in S phase and led to an accumulation of DNA damage including telomere fragility [6] and similar findings were observed in a study involving neuroprogenitors [24]. In a further advance, a somatic knockout of ATRX in a colorectal cell line exhibited increased sensitivity to hydroxyurea and aphidicolin suggesting that in the absence of ATRX there is an increase in replicative stress in this cellular context [25]. Taken together with the findings presented here it is clear that ATRX has a general role in facilitating DNA replication in multiple cellular environments and that this may in part account for why loss of ATRX function results in such disparate pathologies.…”
Section: Discussionsupporting
confidence: 60%
“…Indeed, ATRX targets tandem repeats that preferentially form G-quadruplexes in vitro and unwinds these structures to maintain replication [87]. Consistent with this, ATRX deficiency is associated with replicative stress due to stalled replication forks [88] ( Figure 3A). As mentioned in a previous section, ATRX, together with the histone chaperone DAXX, is required for deposition of histone H3.3 into telomeres.…”
Section: Reviewmentioning
confidence: 82%
“…Other members of this class participate in DNA damage repair pathways, in particular nucleotide excision repair and double-stranded break repair (19). Previous work has shown that ATRX is recruited to sites of DNA damage (20). Thus, we hypothesized that ATRX may play a role in maintaining genetic stability in glioblastoma.…”
Section: Resultsmentioning
confidence: 99%